Solvent-tunable PDMS microlens fabricated by femtosecond laser direct writing. Issue 8 (28th February 2015) - Lu, Dong-Xiao; Zhang, Yong-Lai; Han, Dong-Dong; Wang, Huan; Xia, Hong; Chen, Qi-Dai; Ding, Hong; Sun, Hong-Bo
<x xml:space="preserve">Abstract</x> Reported here is the fabrication of a solvent-tunable polydimethylsiloxane (PDMS) microlens using the femtosecond laser direct writing (FsLDW) technique.